Is it okay to tell? Children's judgements about information disclosure. (24th March 2014) - Kim, Sunae; Harris, Paul L.; Warneken, Felix
<x xml:space="preserve">Abstract</x> The present research investigates how young children evaluate and reason about the disclosure of private information. Using story vignettes, children aged 4–5 and 7–8 years were asked to evaluate an individual who passed on information from a peer revealing that he or she had broken a rule (e.g., stolen a cookie; rule type) or lacked a skill (e.g., could not ride a bicycle; competence type). These negative valence stories were compared with positive valence stories in which the peer had followed a rule or possessed a skill. Younger children approved the sharing of positive, but not negative, information, irrespective of type (rule vs. competence). Older children disapproved the disclosure of someone's incompetence, whereas they approved the disclosure of a rule violation. Children justified their evaluations by reference to social rules in the rule‐type vignettes and to an individual's feelings in the competence‐type vignettes. The findings suggest that young children are concerned about the disclosure of negative information about other people, but with age they become increasingly concerned about protecting the social order even at the cost of individual privacy.